Design and Construction of an Arduino Uno-Based Water pH Level Monitoring System for Coal-Fired Power Plant Boilers - Fadliyani Djaki; Syahrir Abdussamad; Iskandar Zulkarnain Nasibu; Amirudin Yunus Dako (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
The design of an Arduino Uno-based water acidity (pH) monitoring device for boilers at Steam Power Plants (PLTU) fundamentally provides significant assistance to field technicians who monitor water acidity levels daily. Currently, the water sampling process for boilers is generally conducted manually, which is inefficient because the water quality in the boiler fluctuates constantly, while sampling is only performed every eight hours. The objective of this research is to design a pH monitoring device for boilers and display the sensor readings on an LCD monitor. The methodology used in this study involves experimental design for both hardware and software. The hardware utilizes a pH sensor with a pH 4502C module as the input, which is then processed by an Arduino and displayed on the LCD. The results indicate that the pH sensor system using the pH 4502C module can achieve a reading accuracy of up to 95.6%, and the device is considered to be in compliance with national standards. During detection, the sensor monitors pH levels between 7.0 and 11.0; if the level exceeds the 11.0 threshold, the buzzer will deactivate.